Enhancing Coconut Processing Efficiency: Design and Evaluation of A Cost-Effective Coconut De-Husking Machine - Jide Olusegun Adedipe (Jurnal Riset Perkebunan, 2024)
Coconut (Cocos nucifera) plays a crucial role in agricultural economies, particularly in coconut-producing regions, where traditional de-husking methods are labor-intensive and time-consuming. This study focuses on the design, fabrication, and evaluation of a coconut de-husking machine aimed at improving processing efficiency, reducing labor demands, and increasing throughput. The machine was designed to address key performance factors such as frame stability, blade strength, and spring tension. Testing demonstrated that the machine consistently outperformed manual methods, reducing de-husking time to an average of 96.4 seconds compared to 164.8 seconds for traditional techniques. The machine achieved an efficiency rate of 80%, with a throughput capacity of 0.0086 kg/s, significantly higher than the manual method's 0.005 kg/s. Additionally, the machine's cost, approximately N32,000, makes it accessible to smallholder farmers, offering a practical solution for improving productivity and sustainability in coconut farming. The study highlights the potential for mechanized de-husking to transform traditional practices, reduce labor costs, and contribute to economic growth in coconut-rich regions. Future research should explore further optimization of the machine design and its adaptability to different coconut varieties and moisture levels, ensuring broad applicability in diverse farming contexts.